Answer: [tex]\frac{11tc+5g}{66t}=n[/tex]
Step-by-step explanation:
You have the equation [tex]c=6n-\frac{5g}{11t}[/tex].
Then, to solve for the variable [tex]n[/tex] from the equation you need:
Make the subtraction of the right side of the equation:
(As the denominators are 1 and [tex]11t[/tex], the least common denominator is [tex]11t[/tex])
[tex]c=\frac{(6n)(11t)-5g}{11t}\\\\c=\frac{66nt-5g}{11t}[/tex]
Multiply [tex]11t[/tex] to both sides:
[tex](11t)c=(\frac{66nt-5g}{11t})(11t)\\\\11tc=66nt-5g[/tex]
Add [tex]5g[/tex] to both sides:
[tex]11tc+5g=66nt-5g+5g\\\\11tc+5g=66nt[/tex]
And finally divide both sides by [tex]66t[/tex]:
[tex]\frac{11tc+5g}{66t}=\frac{66nt}{66t}\\\\\frac{11tc+5g}{66t}=n[/tex]